Stop bullying! Does gender influence bullying and bully victims? - Azid, N.; Busthami Nur, A. H.; Md-Ali, R.; Kiong, T. T. (LLC Ecological Help, 2022)
The problem and the aims of the study. Every student should not be afraid to go to school because of harassment and parents should not be worried that their children will be bullied while at school. This study aimed to examine whether gender influences Malaysian school students of being bullies or bully victims.